2012
DOI: 10.4269/ajtmh.2012.12-0221
|View full text |Cite
|
Sign up to set email alerts
|

World Health Organization/United Nations Children's Fund Joint Statement on Integrated Community Case Management: An Equity-Focused Strategy to Improve Access to Essential Treatment Services for Children

Abstract: This statement presents the latest evidence for integrated community case management of childhood illness, describes the necessary program elements and support tools for effective implementation, and lays out actions that countries and partners can take to support the implementation of integrated community case management at scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
200
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(205 citation statements)
references
References 14 publications
0
200
0
1
Order By: Relevance
“…One hundred and thirty-two (97.8%) of participants knew that malaria is transmitted through mosquito bite ( Figure 1) and a vast majority of the participants (95.5%) knew that high temperature/fever is a common sign and symptom of malaria ( Figure 2). One hundred and thirty three (98.5%) of the participants knew that sleeping under Tuberculosis [3, [10][11][12][13]. Malaria-related activities provided by CHWs include community education on malaria prevention and diagnosis, distribution of insecticide-treated bed nets and provision of homebased management of malaria [11].…”
Section: Demographic Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…One hundred and thirty-two (97.8%) of participants knew that malaria is transmitted through mosquito bite ( Figure 1) and a vast majority of the participants (95.5%) knew that high temperature/fever is a common sign and symptom of malaria ( Figure 2). One hundred and thirty three (98.5%) of the participants knew that sleeping under Tuberculosis [3, [10][11][12][13]. Malaria-related activities provided by CHWs include community education on malaria prevention and diagnosis, distribution of insecticide-treated bed nets and provision of homebased management of malaria [11].…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…It has been documented that utilizing CHWs could help improve health outcomes for large populations in underserved regions [3, 10,11]. Also, it has been suggested that CHWs are not only cost effective but can enhance the effective implementation of community level health programs especially in the prevention and control of malaria, HIV and…”
Section: Introductionmentioning
confidence: 99%
“…21 This is important because iCCM programs, which have low utilization and likely low acceptance of services are the least costeffective, do not lead to decreases in mortality, and may decrease demand for biomedical health care, leading the most marginalized to seek care from ineffective providers. 1,22 In the current study, we sought to determine the level of community acceptance of CHWs capacity to diagnose and treat sick children with pneumonia at the community level when compared with facility-based health-care workers in western Kenya. Building on the work of other groups in East Africa, 23 we used an adapted version of the Primary Care Assessment Survey (PCAS) 24 to evaluate perceptions of caregivers who sought medical attention for their children with pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…To accelerate progress in reducing underfive child mortality, the World Health Organization (WHO) and the United Nations International Children's Emergency Fund (UNICEF) have recommended the adoption of integrated community case management (iCCM) programs targeting the three major infectious killers of children under 5 yearsdiarrhea, malaria, and pneumonia-to decrease mortality by 70%, 60%, and 90%, respectively, for these conditions. [1][2][3] Though traditionally community health workers (CHWs) have been used to deliver a variety of services including health education, maternal health counseling, and medication monitoring (e.g., directly observed therapy), 4 there has been an increasing emphasis on expanding the role of CHWs to address health workforce deficiencies. iCCM trains lay CHWs to assess, classify, and treat uncomplicated cases of diarrhea, malaria, and pneumonia and refer complicated or severe cases in areas that lack access to prompt and effective treatment due to patient level barriers such as lack of affordable transportation to the health facility, and health system level barriers including both direct and indirect costs.…”
Section: Introductionmentioning
confidence: 99%
“…2 Early and correct treatment for top killer diseases is essential to reduce child mortality where facility-based services alone cannot provide adequate services. 3 Community case management (CCM) involves treatment of selected common childhood diseases by lay community health workers (CHWs). Integrated community case management (iCCM) involves assessment and treatment of more than one illness, using algorithms to manage uncomplicated illnesses including malaria, pneumonia, and diarrhoea.…”
Section: Introductionmentioning
confidence: 99%